Um estudo com professores do ensino médio sobre função modular por meio de resolução de problemas utilizando o software GeoGebra como estratégia pedagógica - Souza, Helena Tavares de (2013)
The purpose of the present paper is to investigate possible contributions to the Basic Education in the teaching of Modular function. To attend such purpose, the investigations were designed in a way so they answer to the research question: In what way the use of a pedagogical strategy based on the problem solving approach of with the software GeoGebra concur to amplify the understanding of High Schools teachers about the Modular Function theme under the algebraic and geometric points of view? This research has a qualitative approach with a content analysis made with four public and private High School teachers, who are also students of a Mathematic Education postgraduate course from a São Paulo s University. The instruments applied to this paper correspond to a semi structured questionnaire divided in four parts and non-structured interviews. The analyses are described under the light of Mathematic Education perspective by solving problems. This research does not focus mainly in the use of technologies, howeveroffers the software GeoGebra as a pedagogical strategy to the teaching of the issue in question. The results point to no differences in the investigated people s ideas related to mathematic problems and exercises; mathematic exercises, for some teachers are exercises, and for others they are mathematic problems, so this also shows that the use of the GeoGebra software concurs to amplify the understanding of some High School teachers about the Modular Function theme